BCG Revaccination to Combat Tuberculosis Infection: an Evidence Based Case Report - Rifa, Alissa; Qomarasandhi, Johan (Writing Center IMERI FMUI, 2023)
An elderly man came to the Emergency Room with labored breathing with a history of prior tuberculosis infection and BCG vaccination when he was an infant. He was diagnosed with tuberculosis reinfection with negative microbiology result. This study aims to see whether revaccination of BCG vaccination will positively impact suppressing the rate of tuberculosis infection. A literature search was conducted on three databases: PubMed, Cochrane, and EBSCOhost. Of the searches, three articles were selected for further critical appraisal using the criteria provided by the University of Oxford Centre of Evidence-Based Medicine. The first study shows that BCG Revaccination does not become a protective factor against tuberculosis reinfection with OR 0.92 (0.80 – 1.05) in all populations yet interestingly yielded OR 0.77 (0.59-1.00) in HIV-negative patients, while the second study shows that BCG Revaccination can prevent conversion of QFT with the study showing p <0.05, thus believed to lower tuberculosis infection rates, the third study shows that BCG revaccination yield modest protection against TB infection after 15 years (Hazard Ratio 0.64 95% CI 0.46-0.89). The main difference between the studies is the main population, which the first study also includes HIV-positive patients. In conclusion, BCG Revaccination may be considered to be given and be considered as protective factor against tuberculosis reinfection in HIV-negative patients.